Inventory System Design at Rajawali Motor Workshop Using Zachman Framework - Setyo Ningtyas, Sulis; Nur Alif, Diah; Pakaja, Fachrudin (International Journal of Information Systems and Technology, 2025)
This research aims to design an inventory system at Rajawali Motor Workshop using the Zachman Framework as an enterprise architecture approach. This research uses qualitative methods with observation, interview, and documentation techniques. The results of the research are in the form of mapping system components based on six perspectives and six components in the Zachman Framework. Each perspective of the actors involved-such as the owner, warehouse admin, chief mechanic, mechanic, cashier, helper, and supplier-has a contribution in designing the system, starting from determining business needs, operational process flow, managing goods data, to distributing information between related parties. The implication of this design is to help the inventory process of goods such as oil, spare parts, and service equipment to be more systematic and integrated. This research is also the basis for implementing an information system that supports the business needs of the workshop.